PYRITINOL USAGE IN PEDIATRIC NEUROLOGY - N. N. Zavadenko; Yu. E. Nesterovskii; E. V. Kozlova ("Paediatrician" Publishers LLC, 2013)
Treatment of developmental disorders, correction of learning disabilities and behavioral problems in children should be prompt, complex and include pharmacotherapy with nootropic agents. The results of recent studies shown in this review proved effectiveness of pharmacotherapy with pyritinol in children with perinatal injury of central nervous system and its consequences, psychomotor and speech development delay, dyslexia, attention deficit/hyperactivity disorder, cognitive disorders and learning disabilities (including manifestations of epilepsy, chronic tic disorders and Tourette syndrome). Due to its ability to optimize metabolic processes in central nervous system, pyritinol is used in treatment of vegetative dysfunction in children and adolescents, especially associated with asthenical manifestations, as well as in complex therapy of exertion headache and migraine. The drug is effective in treatment of cognitive disorders in children and adolescents with epilepsy, pyritinol was administered without changing of the basic anticonvulsive therapy and no deterioration (increase of severity of seizures or intensity of epileptiform activity on electroencephalogramms) was observed. Significant nootropic effect of pyritinol, including neurometabolic, neuroprotective, neurodynamic and other mechanisms, in association with safety and rare side effects of this drug determines its wide usage in pediatric neurology.